2014
DOI: 10.1603/en13237
|View full text |Cite
|
Sign up to set email alerts
|

Traps and Trap Placement May Affect Location of Brown Marmorated Stink Bug (Hemiptera: Pentatomidae) and Increase Injury to Tomato Fruits in Home Gardens

Abstract: The invasive brown marmorated stink bug, Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), is an important pest of field crops, fruit orchards, commercial vegetables, ornamental plants, and home vegetable gardens. Pheromone-baited traps designed to attract, trap, and kill H. halys are marketed for use in home gardens to reduce damage to plants. To test this assertion, we conducted the following experiment: One group of 15 gardeners placed stink bug traps at the end of a row of tomatoes, Solanum lycopersicum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Our findings showed that H. halys can be aggregated to spatially precise locations in an orchard and successfully removed from the population through regular insecticide applications. These results are encouraging as other studies showed that damage increased in the vicinity of MDT-baited traps for H. halys in tomato compared with unbaited plots (Sargent et al 2014). The risk of widespread damage from adults in these attract-and-kill trees in grower orchards is potentially minimal, at least with the important caveat that growers need to treat the directly adjacent trees with efficacious materials to suppress any potential damage that may arise around the baited attract-and-kill tree.…”
Section: Discussionsupporting
confidence: 51%
“…Our findings showed that H. halys can be aggregated to spatially precise locations in an orchard and successfully removed from the population through regular insecticide applications. These results are encouraging as other studies showed that damage increased in the vicinity of MDT-baited traps for H. halys in tomato compared with unbaited plots (Sargent et al 2014). The risk of widespread damage from adults in these attract-and-kill trees in grower orchards is potentially minimal, at least with the important caveat that growers need to treat the directly adjacent trees with efficacious materials to suppress any potential damage that may arise around the baited attract-and-kill tree.…”
Section: Discussionsupporting
confidence: 51%
“…A possible means for reducing BMSB populations is to have citizen volunteers deploy small, pyramid-style pheromone traps to maximize the insect catches in nearby urban settings [46]. These preventive control measures should be diapause-aware, meaning that they could be executed in spring and late-fall, to gradually reduce the pest population and minimize the damage caused to sensitive crops throughout the season [47].…”
Section: Citizens' Impactmentioning
confidence: 99%
“…Semiochemicals have been examined for their potential as management tools for H. halys (Khriman et al 2014;Sargent et al 2014;Weber et al 2014;Zhang et al 2014). In particular, identification of the aggregation pheromone of H. halys and its synergistic effects with methyl (2E,4E,6Z)-decatrienoate offers new opportunities for management of this invasive pest (Khriman et al 2014;Weber et al 2014).…”
Section: Semiochemicalmentioning
confidence: 99%
“…In the US, pheromone-baited traps designed to attract, trap, and kill H. halys are marketed for use in home gardens. This assertion was tested in home tomato gardens; however, the study found that tomato fruits in gardens with traps sustained significantly more injury than those without traps (Sargent et al 2014). This highlights how essential it is to establish the distance of attraction of H. halys by pheromones, so that the location and number of traps can be properly adjusted depending on the configuration and size of crop fields.…”
Section: Semiochemicalmentioning
confidence: 99%